2010
DOI: 10.1002/cncr.25047
|View full text |Cite
|
Sign up to set email alerts
|

Varying recurrence rates and risk factors associated with different definitions of local recurrence in patients with surgically resected, stage I nonsmall cell lung cancer

Abstract: BACKGROUND:The objective of this study was to examine the effects of different definitions of local recurrence on the reported patterns of failure and associated risk factors in patients who undergo potentially curative resection for stage I nonsmall cell lung cancer (NSCLC). METHODS: The study included 306 consecutive patients who were treated from 2000 to 2005 without radiotherapy. Local recurrence was defined either as ''radiation'' (r-LR) (according to previously defined postoperative radiotherapy fields),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 36 publications
0
40
1
Order By: Relevance
“…For example, 5-year loco-regional recurrence rates are between 15 and 38.5% [2], and the incidence of local recurrence in early-stage lung cancer of 10-15% [3], or a mean disease-free interval of 14.1-19.8 months, that is similar to distant recurrent disease [4]. Failure to demonstrate the advantage of complete lymphadenectomy over nodal sampling in terms of local recurrence or survival in patients operated for T1-2, N0 or T1-2, N1 disease, makes the clinical approach more complex [5].…”
Section: @Erspublicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 5-year loco-regional recurrence rates are between 15 and 38.5% [2], and the incidence of local recurrence in early-stage lung cancer of 10-15% [3], or a mean disease-free interval of 14.1-19.8 months, that is similar to distant recurrent disease [4]. Failure to demonstrate the advantage of complete lymphadenectomy over nodal sampling in terms of local recurrence or survival in patients operated for T1-2, N0 or T1-2, N1 disease, makes the clinical approach more complex [5].…”
Section: @Erspublicationsmentioning
confidence: 99%
“…The worse survival rates reported, for example 23% in one series, are counterweighted by the high proportion (>65%) of stage III patients. The evidence indicates better survival of patients with squamous cell versus adenocarcinoma [2] and a significant influence of disease stage (stages I and II versus stage III).…”
mentioning
confidence: 99%
“…Some studies limit the definition of local recurrences to those found in the bronchial stump, staple line, ipsilateral hilum, and ipsilateral mediastinum [5]. Others have expanded this definition to include the entire ipsilateral lung and contralateral hilar and mediastinal lymph nodes [6]. Still many others provide no clear description of how local recurrence was defined in determining results.…”
Section: The Definition Of Local Recurrencementioning
confidence: 99%
“…Diabetes mellitus (DM) and cardiovascular diseases have been reported to place patients undergoing curative resection at higher risk of local recurrence and reduced survival (6,7). In addition, patients receiving curative surgery for their NSCLC who have co-existing chronic obstructive pulmonary disease (COPD) have worse survival than their counterparts with a better pulmonary function (8).…”
mentioning
confidence: 99%